Gynecological cancer patients' differentiated use of help from a nurse navigator: a qualitative study - Thygesen Marianne K; Pedersen Birthe D; Kragstrup Jakob; Wagner Lis; Mogensen Ole (BMC, 2012)
Abstract Background Fragmentation in healthcare can present challenges for patients with suspected cancer. It can add to existing anxiety, fear, despair and confusion during disease trajectory. In some circumstances patients are offered help from an extra contact person, a Nurse Navigator (NN). Scientific studies showing who will benefit from the extra help offered are missing. This study aims to explore who could benefit from the help on offer from a nurse appointed as NN in the early part of a cancer trajectory, and what would be meaningful experiences in this context. Methods A longitudinal study with a basis in phenomenology and hermeneutics was performed among Danish women with gynecological cancer. Semi-structured interviews provided data for the analysis, and comprehensive understanding was arrived at by first adopting an open-minded approach to the transcripts and by working at three analytical levels. Results Prior experience of trust, guarded trust or distrust of physicians in advance of encountering the NN was of importance in determining whether or not to accept help from the NN. For those lacking trust in physicians and without a close relationship to a healthcare professional, the NN offered a new trusting relationship and they felt reassured by her help. Conclusions Not everyone could use the help offered by the NN. This knowledge is vital both to healthcare practitioners and to administrators, who want to do their best for cancer patients but who are obliged to consider financial consequences. Moreover patients' guarded trust or distrust in physicians established prior to meeting the NN showed possible importance for choosing extra help from the NN. These findings suggest increased focus on patients' trust in healthcare professionals. How to find the most reliable method to identify those who can use the help is still a question for further debate and research.